Mathematics. Course 3 - Bennett, Jennie M. (Orl. Holt McDougal Houghton Mifflin Harcourt, 2012)
Principles of algebra; Rational numbers; Graphs and functions; Exponents and roots; Ratios, proportions, and similarity...
Keywords: Mathematics -- Study and teaching